Tool for virtual engineering - Wolfgang Mueller-Wittig. (2008)
The Centre for Advanced Media Technology?s task in the project was the development of a 3D visualization of a virtual factory, which aims to support decision makers to understand, explore and experiment with the virtual factory. During the project CAMTech built up a library of models of equipment commonly used in assembly and logistic processes. The original objects where chosen, measured and photographed at the industrial project partner?s manufacturing plant. They were then created as 3D models with the use of commercially available 3D software. In the beginning CAMTech made a review of existing visualization systems for discrete simulation results. From several evaluated systems the CASUS system was chosen. The 3D models were imported into the CASUS Base library and extended with animation behavior functionality. The shop floor was laid out. The animation behavior was linked with the simulation events and the CASUS system generated the animation sequence that visualized the simulation results. The CASUS system already produced animations in a satisfying quality and demonstrated the usefulness of simulation result visualization in 3D animations.